The Factors Lead to Management Accounting Change: A Malaysian Perspective - Chen, Gengqiu (2007)
In recent years, management accounting change has dominated both the professional and academic accounting literature. This paper aims to explore what are the factors leads to management accounting changes in Malaysian companies over the period 1997-2007. Data collected through online survey questionnaire administered to 1449 member of the Malaysian Institute of Accountants (MIA) who has the Chartered Institute of Management Accountants (CIMA) qualification. In all, 30 professionally qualified management accountants responded to the online survey questionnaire, but only 15 are usable. A case based reasoning methodology is used to compare the survey sample with literature cases indicate that, there are similarities and dissimilarities in change of management accounting systems or technique under the similar situation. The study prove that, the change of management accounting system or technique in Malaysia are influence by common change factors cited in literature such as globalization, information technology, core competency aims, quality initiatives, and etc. Moreover, the dissimilarities of management accounting change between companies are explain by factors such as difference in roles of management accountant within the organization, difference in activities of management accountant involved, difference in management accountants’ skills, difference in size of company, difference in industry, difference in experience of management accountant, difference in geographic locations of company, difference in stage of management accounting development in organization, and difference in position of management accountant in organization. The findings of this paper has in congruence with institutional theory and contingency theory studies on management accounting change, prove that, the change of management accounting are organizational response to macro and micro level (and/or external and internal level) change of institutional environment. In addition, this finding prove that, there is no universally appropriate accounting system applicable to all organizations in all circumstance, the particular features of an appropriate accounting system will depend upon the specific circumstance in which an organization finds itself.